ETHNIC IDENTITY AND ETHNIC CULTURE AMONG THE RESIDENTS OF EASTERN LATVIA - Makarevičs, Valērijs; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Ethnic identity is an important component of a person’s personal identity. Many studies indicate that a strong and secure ethnic identity positively correlates with an adequate self-esteem, coping mechanisms, and optimism. In this study the authors intend to analyse the socio-psychological theories of the ethnic group, ethnic identity and the relationship of ethnic identity and ethnic culture. This article reflects findings gained as a result of a comparative analysis of the characteristics of ethnic identity and its connectedness with ethnic culture among the students of Eastern Latvia. The authors identify what is common for the ethnic groups of the region, as well as point to the differences in the perceptions of their ethnic identity and its manifestation among the respondents. Research methodology: The authors developed a methodology that combines quantitative and qualitative methods of processing the results. This article reflects part of the data obtained as a result of conducting inquiry, where respondents were asked to name literary works in which their ethnic character is reflected most vividly, as well as to name traditions that corresponds to their ethnic identity. The results of the study suggest that there is an idea of the ideal ethnic character and its manifestation. The ethnic traditions, mentioned by the respondents who has Latvian as their native language, were associated with nature, cyclical rhythms in nature and religious symbols. As for the respondents who had Russian as their mother tongue, the most significant were such public holidays such as the New Year, as well as traditional religious festivals.